Reinforcement of Timber Beams with Steel Bars: Parametric Analysis Using the Finite Element Method - Christoforo, André Luis; Gomes, Arthur Filipe Freire; Arroyo, Felipe Nascimento; Mascarenhas, Fernando Júnior Resende; Santos, Herisson Ferreira dos; Topolniak, Luciano; Akasaki, Jorge Luis [UNESP] (MDPI, 2022)
Incorporating steel bars as reinforcement in glued laminated timber beams is a technique that aims at better structural performance, allowing the reduction of cross-sections. In the present research, based on experimental results from literature about the reinforcement of timbers beams, a parametric study was carried out with the aid of 164 numerical simulations performed within the scope of linear and nonlinear physical analysis via the finite element method to evaluate, with the aid of analysis of variance (ANOVA), the span, base, height, and the reinforcement ratio influence in the service force, ultimate force, and ultimate displacement. Multiple regression models evaluated by ANOVA were established to estimate the service and ultimate forces and ultimate and service displacements as a function of other variables. The results showed an average increase in the service load of 32% and 49%, and the ultimate load of 42.90% and 66.90%, for reinforcement rates of 2% and 4%, respectively. Regarding the multiple regression models, due to the good values obtained from the adjusted determination coefficients to estimate the values of the forces and the ultimate displacements, these can be used in the pre-design of glued laminated timber beams reinforced with steel bars.
Keywords: ABAQUS; ANOVA; Hill’s failure criteria; structural reinforcement